Results of the anonymous questionnaire of dentists from Ukraine on the section of endodontics. Part 1. - Skibitska, O.; Hennavi В.; Krupych, M. (Actual Dentistry, 2018)
Objective: the study of the prevalence of root canal system irrigation agents and methods in the process of endodontic treatment by practicing dentists in Ukraine through anonymous questionnaires. Object and methods. An endodontic section questionnaire, which is rarely distributed in the print format among dentists of Ukraine. Also, in the form of a Googleform posted on the social network Facebook and sent, on the electronic mailing addresses of dental clinics and medical universities of Ukraine. Results. During the course of work, 1273 questionnaires were filled completely, respondents with different experience and place of work. The most commonly used solutions for irrigation of root canal system during endodontic treatment are sodium hypochlorite and chlorhexidine begluconate, respectively, 83.39 % and 36.57 % of doctors include them in the irrigation protocol, regardless of experience and place of work. Chelate EDTA solutions of 57.40 % and citric acid in 32.86 % of cases are used by physicians in combination with sodium hypochlorite or chlorhexidine begluconate. The most common method of irrigation, which uses 68.64 % of physicians, regardless of the work experience, is a syringe and an endoneedles. Also, 14.92 % of doctors use the EndoVas negative pressure system, along with the syringe and endodontic tube. 63.43 % of doctors conduct ultrasonic activation of solutions for irrigation, 20.14 % of physicians do not activate the irrigation solution during endodontic treatment. Conclusions. A high percentage of doctors in Ukraine in their practice use common means and methods of irrigation of the root canal system during endodontic treatment. That is, a combination of sodium hypochlorite with EDTA chelates or citric acid, a syringe with an endoneedles, and activates the solutions using an ultrasound method. However, a certain percentage of physicians use ineffective means and outdated root canal system irrigation techniques, which greatly reduces the quality of endodontic treatment and increases the risk of complications of periapical tissues. Perhaps, given the economic availability and proven effectiveness of more modern means and methods of irrigation, these doctors need to review their approaches to endodontic treatment. Key words: anonymous questionnaire, endodontics, agents of irrigation, methods of irrigation, dentists of Ukraine.